Antibody response in children with multisystem inflammatory syndrome related to COVID-19 (MIS-C) compared to children with uncomplicated COVID-19 - Thiriard, Anaïs; Meyer, Benjamin; Eberhardt, Christiane S.; Loevy, Natasha; Grazioli, Serge; Adouan, Wafae; Fontannaz, Paola; Marechal, Fabienne; L’Huillier, Arnaud G.; Siegrist, Claire-Anne; Georges, Daphnée; Putignano, Antonella; et al. (Frontiers in Immunology, 2023)
Objectives: To comprehensively analyze the quality of the antibody response between children with Multisystem inflammatory syndrome (MIS-C) and age-matched controls at one month after SARS-CoV-2 exposure, and infected in the same time-period. Methods: Serum from 20 MIS-C children at admission, and 14 control children were analyzed. Antigen specific antibody isotypes and subclasses directed against various antigens of SARS-CoV-2 as well as against human common coronavirus (HCoVs) and commensal pathogens were assessed by a bead-based multiplexed serological assay and by ELISA. The functionality of these antibodies was also assessed using a plaque reduction neutralization test, an RBD-specific avidity assay, a complement deposition assay and an antibody-dependent neutrophil phagocytosis (ADNP) assay. Results: Children with MIS-C developed a stronger IgA antibody response in comparison to children with uncomplicated COVID-19, while IgG and IgM responses are largely similar in both groups. We found a typical class-switched antibody profile with high level of IgG and IgA titers and a measurable low IgM due to relatively recent SARS-CoV-2 infection (one month). SARS-CoV-2-specific IgG antibodies of MIS-C children had higher functional properties (higher neutralization activity, avidity and complement binding) as compared to children with uncomplicated COVID-19. There was no difference in the response to common endemic coronavirus between both groups. However, MIS-C children had a moderate increase against mucosal commensal and pathogenic strains, reflecting a potential association between a disruption of the mucosal barrier with the disease. Conclusion: Even if it is still unclear why some children develop a MIS-C, we show here that MIS-C children produce higher titers of IgA antibodies, and IgG antibodies with higher functionality, which could reflect the local gastro-intestinal mucosal inflammation potentially induced by a sustained SARS-CoV-2 gut infection leading to continuous release of SARS-CoV-2 antigens.